Effects of cross-mating on susceptibility of synonymous mosquitoes, Anopheles paraliae and Anopheles lesteri to infection with nocturnally subperiodic Brugia malayi - Watcharatip Dedkhad (2018)
© 2018 Elsevier B.V. In Southeast Asia, Anopheles lesteri (recently synonymized with An. paraliae) is a competent vector for Plasmodium parasites, but its ability to transmit parasites that cause lymphatic filariasis has yet to be determined. In this study, the susceptibility of An. lesteri and An. paraliae to Brugia malayi parasites was determined by comparing with the control mosquito, Aedes togoi. We found that the infection prevalence per infected mosquito in An. paraliae was significantly lower than that in Ae. togoi in all experiments (p < 0.05). Reciprocal crosses (female An. paraliae x male An. lesteri) produced highly susceptible F1-hybrid progeny, with increased infection prevalence when compared to parental stocks (p < 0.05). Subsequently, the possibilities of introgression between high and low/moderate parasite susceptibility genes were investigated by cross-mating experiments (parental, reciprocal crosses, back crosses and repeated backcrosses). The results showed the possibility of introgression of B. malayi-susceptible genes between An. paraliae (low/moderate susceptibility) and An. lesteri (high susceptibility) based on increasing or decreasing susceptibility and normal larval development in the thoracic muscles of F3-hybrids. Additionally, melanization, an innate immune response with proven involvement in the susceptibility or refractoriness of mosquitoes to B. malayi parasites, was examined. Parasite degeneration and cell aggregation, and melanization were observed for first-stage larvae in the thoracic muscle fibers of hybrid mosquitoes.